Integrating Digital Leadership in Micro Leading Course to Enhance MPI Students’ Graduate Competencies at UIN Sultanah Nahrasiyah Lhokseumawe - Zulkhairi Zulkhairi; Rahima Nurviani (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2026)
The changing digital era brings the needs for graduates to focus not only on good academic results, but also on the competence required to compete in the workforce. Therefore, this study aimed to investigate how the integration of digital leadership can enhance the competence of graduates in Islamic Education Management (MPI) at Islamic State University Sultanah Nahrasiyah Lhokseumawe. This qualitative research used depth interviews, participatory observation, and documentation as the techniques to collect the data. Meanwhile, four students who enrolled in Micro Leading courses were involved as research participants. This research found that the students in the Micro Leading course at MPI cultivated digital leadership skills by observing schools. These hands-on experiences with digital tools and organizational digitalization prompted MPI students to concur that adopting digital leadership improves future graduate skills, cultivating a profound comprehension of seamless technology integration, and the creation of digital organizations, thereby equipping them for a fast-paced, digitally-oriented job market.